Functionalized porous silica&maghemite core-shell nanoparticles for applications in medicine: design, synthesis, and immunotoxicity - Zasonska, Beata A; Líškova, Aurelia; Kuricova, Miroslava; Tulinska, Jana; Pop-Georgievski, Ognen; Čiampor, Fedor; Vavra, Ivo; Dušinska, Maria; Ilavska, Silvia; Horvathova, Mira; Horák, Daniel (Croatian medical journal, 2016)
AIM: To determine cytotoxicity and effect of silica-coated magnetic nanoparticles (MNPs) on immune response, in particular lymphocyte proliferative activity, phagocytic activity, and leukocyte respiratory burst and in vitro production of interleukin-6 (IL-6) and 8 (IL-8), interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), and granulocyte macrophage colony stimulating factor (GM-CSF). METHODS: Maghemite was prepared by coprecipitation of iron salts with ammonia, oxidation with NaOCl and modified by tetramethyl orthosilicate and aminosilanes. Particles were characterized by transmission electron microscopy (TEM), dynamic light scattering (DLS), Fourier-transform infrared (FTIR), and X-ray photoelectron spectroscopy (XPS). Cytotoxicity and lymphocyte proliferative activity were assessed using [3H]-thymidine incorporation into DNA of proliferating human peripheral blood cells. Phagocytic activity and leukocyte respiratory burst were measured by flow cytometry; cytokine levels in cell supernatants were determined by ELISA. RESULTS: γ-Fe2O3&SiO2-NH2 MNPs were 13 nm in size. According to TEM, they were localized in the cell cytoplasm and extracellular space. Neither cytotoxic effect nor significant differences in T-lymphocyte and T-dependent B-cell proliferative response were found at particle concentrations 0.12-75 μg/cm2 after 24, 48, and 72 h incubation. Significantly increased production of IL-6 and 8, and GM-CSF cytokines was observed in the cells treated with 3, 15, and 75 µg of particles/cm2 for 48 h and stimulated with pokeweed mitogen (PHA). No significant changes in TNF-α and IFN-γ production were observed. MNPs did not affect phagocytic activity of monocytes and granulocytes when added to cells for 24 and 48 h. Phagocytic respiratory burst was significantly enhanced in the cultures exposed to 75 µg MNPs/cm2 for 48 h. CONCLUSIONS: The cytotoxicity and in vitro immunotoxicity were found to be minimal in the newly developed porous core-shell γ-Fe2O3&SiO2-NH2 magnetic nanoparticles.
Keywords: železité sloučeniny; fagocyty; Male; Silicon Dioxide; Phagocytes; Tumor Necrosis Factor-alpha; Ferric Compounds; Structure-Activity Relationship; Interleukin-8; respirační vzplanutí; faktor stimulující granulocyto-makrofágové kolonie; Interleukin-6; mužské pohlaví; lymfocyty; nanoslupky; Flow Cytometry; Respiratory Burst; vztahy mezi strukturou a aktivitou; leukocyty; průtoková cytometrie; lidé; Humans; interleukin-6; Lymphocytes; Leukocytes; interleukin-8; Granulocyte-Macrophage Colony-Stimulating Factor; oxid křemičitý; TNF-alfa; Nanoshells